2022
DOI: 10.1038/s41405-022-00116-6
|View full text |Cite
|
Sign up to set email alerts
|

Peer-assessment ability of trainees in clinical restorative dentistry: can it be fostered?

Abstract: Objectives The study was conducted to investigate whether peer-assessment among dental students at the clinical stage can be fostered and become closer to that of experienced faculty assessors. Methods A prospective pilot study was conducted in 2021 at the Faculty of Dentistry, Damascus University. Sixteen 5th year clinical students volunteered to participate in the study. A modified version of the validated Peer Direct Observation of Procedural Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We found that there was a significant difference between the overall quality of peer feedback as compared to instructor feedback. The quality of qualitative forms of peer feedback is not frequently assessed in the broader literature, although differences in quantitative peer feedback is mixed, with some publications supporting a difference between peer and instructor 10,18 and others finding no significant difference. 3,[19][20][21] We suspect this is a multifactorial problem that varies based on task, institution, and the specifics of the course.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was a significant difference between the overall quality of peer feedback as compared to instructor feedback. The quality of qualitative forms of peer feedback is not frequently assessed in the broader literature, although differences in quantitative peer feedback is mixed, with some publications supporting a difference between peer and instructor 10,18 and others finding no significant difference. 3,[19][20][21] We suspect this is a multifactorial problem that varies based on task, institution, and the specifics of the course.…”
Section: Discussionmentioning
confidence: 99%